Expression and Function Studies of CYC/TB1-Like Genes in the Asymmetric Flower Canna (Cannaceae, Zingiberales) - Yu, Qianxia; Tian, Xueyi; Lin, Canjia; Specht, Chelsea D.; Liao, Jingping (Frontiers in Plant Science, 2020)
The asymmetric flower, lacking any plane of symmetry, is rare among angiosperms. Canna indica L. has conspicuously asymmetric flowers resulting from the presence of a half-fertile stamen, while the other androecial members develop as petaloid staminodes or abort early during development. The molecular basis of the asymmetric distribution of fertility and petaloidy in the androecial whorls remains unknown. Ontogenetic studies have shown that Canna flowers are borne on monochasial (cincinnus) partial florescences within a racemose inflorescence, with floral asymmetry likely corresponding to the inflorescence architecture. Given the hypothesized role of CYC/TB1 genes in establishing floral symmetry in response to the influence of the underlying inflorescence architecture, the spatiotemporal expression patterns of three Canna CYC/TB1 homologs (CiTBL1a, CiTBL1b-1, CiTBL1b-2) were analyzed during inflorescence and floral development using RNA in situ hybridization and qRT-PCR. In the young inflorescence, both CiTBL1a and CiTBL1b-1 were found to be expressed in the bracts and at the base of the lateral florescence branches, while transcripts of CiTBL1b-2 were mainly detected in flower primordia and inflorescence primordia. During early flower development, expression of CiTBL1a and CiTBL1b-1 were both restricted to the developing sepals and petals. In later flower development, expression of CiTBL1a was reduced to a very low level while CiTBL1b-1 was detected with extremely high expression levels in the petaloid androecial structures including the petaloid staminodes, the labellum, and the petaloid appendage of the fertile stamen. In contrast, expression of CiTBL1b-2 was strongest in the fertile stamen throughout flower development, from early initiation of the stamen primordium to maturity of the ½ anther. Heterologous overexpression of CiTBL genes in Arabidopsis led to dwarf plants with smaller petals and fewer stamens, and altered the symmetry of mature flowers. These data provide evidence for the involvement of CYC/TB1 homologs in the development of the asymmetric Cannaceae flower.